Pengaruh Disiplin Kerja Terhadap Kinerja Karyawan Pada PT. Tri Samudra Ambon - Alda Semarang; Olivia Laura Sahertian; Maria Marlyn Tetelepta (P3M Politeknik Negeri Ambon, 2024)
Employee performance is influenced by and enhanced by work discipline. The purpose of this study is to ascertain how PT. Tri Samudra Ambon employees perform in relation to work discipline.Using the Slovin formula, a sample of 90 respondents was selected. Simple linear regression analysis and descriptive analysis using SPSS software were the analytical techniques employed in this study. The derived regression is Y = 4.630 + 0.784. Descriptive analysis indicates that employee performance at PT. Tri Samudra Ambon has an average score of 3.34, which is regarded as good, and work discipline has an average score of 3.27, which is quite good.These findings support the notion that PT. Tri Samudra staff performance is positively impacted by discipline. Keywords: Work Discipline, Employee Performance